Determination of Elastic Moduli and Geotechnical Parameters of the Upper Soil Layer Using Ultrasonic Waves in Al- Jadiriyah Area - University of Baghdad-Iraq - Khorshid , Salman Zainal -Abdin (Iraqi Journal of Science, 2022)
Analysis and determination of some of the elastic moduli and other geotechnical parameters in the campus of the University of Baghdad performed by using New Sonic Viewer in the field to measure (Vp) and (Vs) velocities as well as the density of the upper soil inside the campus. Seventeen profiles were selected each of (10) m. length distributed randomly inside the university campus to evaluate the top soil properties in addition to the soil profile.The ultrasonic waves showed two layers of the soil with different velocities of(Vp) and (Vs). The velocities of p-wave of the first layer ranged from (288-642) m/sec. On other hand the velocities of shear wave (Vs) in the same layer ranged from (88-193) m/sec. In the second layer the velocities of p-wave ranged from (681-972) m/sec., and the velocities of shear wave ranged from (327-463) m/sec.Depending upon the value of (Vs) and according to Caltrans soil types, these two layers were considered as soft and stiff soils of types ( E and D) respectively. The mean depth of the first layer in the area is (1.91) m. The densities of the first layer ranged from (1743-1999) Kg/m3.The values of Poisson's ratio, Young's modulus, Shear modulus, Lame's constant, Bulk modulus and Compressibility are also determined as well as some of geotechnical properties as earth lateral pressure at rest (KO), Concentration index, Ultimate bearing capacity, Material index, and the empirical relation was used to calculate (N) values of the standard penetration test (SPT) from shear wave velocities and its value ranged for the first layer from (2-35) b/30 cm. and for second layer the (N) values ranged from (25-45) b/cm., as well as the relationship between the most important geotechnical and elastic modulus with their equations on each graph